Biomechanical analysis of hypoplastic left heart syndrome and calcific aortic stenosis: a statistical and computational study - Zebhi, Banafsheh, author; Bark, David, advisor; Gao, Xinfeng, committee member; Wang, Zhijie, committee member; Scansen, Brian, committee member (Colorado State University. Libraries, 2021)
Cardiovascular diseases are a leading cause of death in the United States. In this dissertation, a congenital heart disease (CHD) and a valvular disease are discussed. CHDs occur in ~5% of live births. Structural CHDs can be complex and difficult to treat, such as hypoplastic left heart syndrome (HLHS) in which the left ventricle is generally underdeveloped, representing ~9% of all congenital heart diseases. Calcific aortic stenosis is one of the most common valvular diseases in which valves thicken and stiffen, and in some cases nodular deposits form, limiting valve function that may result in flow regurgitation and outflow obstruction. The overarching hypothesis of this research is that patient-specific heart geometry and valve characteristics are linked to cardiovascular diseases and may play an important role in regulating hemodynamics within the heart. This hypothesis is studied through three specific aims. In specific aim 1, a computational fluid dynamics study was developed to quantify the hemodynamic characteristics within the right ventricles of healthy fetuses and fetuses with HLHS, using 4D patient-specific ultrasound scans. In these simulations, we find that the HLHS right ventricle exhibits a greater cardiac output than normal; yet, hemodynamics are relatively similar between normal and HLHS right ventricles. Overall, this study provides detailed quantitative flow patterns for HLHS, which has the potential to guide future prevention and therapeutic interventions, while more immediately providing additional functional detail to cardiologists to aid in decision making. The specific aim 2 is a comprehensive review in which we highlight underlying molecular mechanisms of acquired aortic stenosis calcification in relation to hemodynamics, complications related to the disease, diagnostic methods, and evolving treatment practices for calcific aortic stenosis and, bioprosthetic or native aortic scallop intentional laceration (BASILICA) procedure to free coronary arteries from obstruction. In specific aim 3, we use statistical trends and relationships to identify the role of patient-specific aortic valve characteristics in post-BASILICA coronary obstruction. The findings of this study shows that in addition to direct anatomical measurements of the aortic valve, the aspect ratios of the anatomical features are important in determining the cause of post-BASILICA coronary obstruction. The overall significance of this dissertation is that computational and statistical analysis of patient's specific flow hemodynamics and geometric characteristics can provide more insight into the cardiovascular disease and treatment approaches which can ultimately assist surgeons with procedural planning.
Zip file contains supplementary videos, no sound.
Keywords: congenital heart disease; valvular disease; heart geometry; valve characteristics; hemodynamics; computational fluid dynamics